2003
DOI: 10.1074/jbc.m301152200
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Heparan Sulfate Participates in the Metabolism of Prions

Abstract: During prion diseases, the host protein PrPC is refolded into an abnormal conformer "prion" PrP Sc . Histological and pharmacological data have suggested that glycosaminoglycans may be involved in the development of prion diseases. Here we present the first direct evidence that cellular glycosaminoglycans play a role in the biogenesis of PrP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
124
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(126 citation statements)
references
References 74 publications
(92 reference statements)
2
124
0
Order By: Relevance
“…supported by experiments showing that FabЈ fragments of some of these antibodies failed to immunoprecipitate PrPsc. This is not surprising taking into account that several proteins and polymers have already been shown to bind SAFs, including serum proteins (12), heparan sulfates (13,14), and nucleic acids (4,15). In addition, we show that a significant PrPsc immunoprecipitation can be obtained even with BSA-coated beads in appropriate conditions.…”
Section: Discussionmentioning
confidence: 75%
“…supported by experiments showing that FabЈ fragments of some of these antibodies failed to immunoprecipitate PrPsc. This is not surprising taking into account that several proteins and polymers have already been shown to bind SAFs, including serum proteins (12), heparan sulfates (13,14), and nucleic acids (4,15). In addition, we show that a significant PrPsc immunoprecipitation can be obtained even with BSA-coated beads in appropriate conditions.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, the restricted range of neuronal and nonneuronal cell types that are susceptible to infection by prions also suggests the existence of prion propagation cofactors (11)(12)(13). Although no specific cofactors have been identified to date, several studies have shown that various polyanionic compounds, such as host-encoded RNA and proteoglycan molecules, appear to stimulate prion-seeded conversion of PrP C into PrP Sc molecules in vitro (10,(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Several lines of in vitro and in vivo evidences suggest that binding of PrP to GAG is important in the conversion process, and thus critical for pathogenesis (30)(31)(32)(33). PrP Sc in vivo contains GAG (34).…”
Section: Discussionmentioning
confidence: 99%